Circ‐HOMER1 enhances the inhibition of miR‐1322 on CXCL6 to regulate the growth and aggressiveness of hepatocellular carcinoma cells. Issue 11 (9th February 2020) - Zhao, Mingyu; Dong, Guanglong; Meng, Qingyu; Lin, Shusen; Li, Xichun
Abstract: Hepatocellular carcinoma (HCC) is a common liver malignancy worldwide accompanying with the high rate of recurrence. Accumulating reports have documented the significance of circular RNAs (circRNAs) in carcinogenesis and development of HCC. This study aimed to establish the mechanism underlying circ‐HOMER1 involvement in HCC. To this end, we identified a binding site for miR‐1322 via bioinformatics, quantitative reverse transcriptase‐polymerase chain reaction (qRT‐PCR), and dual‐luciferase reporter assays providing evidence of a direct link between circ‐HOMER1 and miR‐1322. Similarly, the target gene of miR‐1322 was investigated. Moreover, we determined the specific function of circ‐HOMER1 in HCC with the aid of qRT‐PCR based on patient clinical records, Cell Counting Kit‐8, acridine orange/ethidium bromide double fluorescence staining, flow cytometry, and wound‐healing and transwell assays. Notably, circ‐HOMER1 was upregulated in both HCC cells and tissues. This aberrant expression pattern was closely correlated with larger tumor size, higher tumor‐node‐metastasis stage, and poorer prognosis for the patients with HCC. Moreover, silenced circ‐HOMER1 inhibited cell proliferation, migration, and invasion concomitant with the promotion of apoptosis in HCC cells, and vice versa. Mechanistically, circ‐HOMER1 enhanced the inhibition of miR‐1322 on CXCL6 in HCC. Furthermore, we found that circ‐HOMER1 promoted HCC cell growth and aggressiveness by miR‐1322/CXCL6 axis. This study may provide a potential prognostic indicator and therapeutic target for patients with HCC. Abstract : 1. Circular‐HOMER1 (circ‐HOMER1) is upregulated in hepatocellular carcinoma (HCC) tissues and cell lines. 2. circ‐HOMER1 promotes cell growth, migration, and invasion but inhibit cell apoptosis in HCC cells. 3. circ‐HOMER1 enhances the inhibition of miR‐1322 on CXCL6 in HCC. 4. circ‐HOMER1 facilitates HCC cell proliferation and aggressiveness by miR‐1322/CXCL6 axis.